2022
DOI: 10.1039/d2tb01464e
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic-based functional materials: new prospects for wound healing and beyond

Abstract: Microfluidics has been applied to fabricate high-performance functional materials contributing to all physiological stages of wound healing. The advances of microfluidic-based functional materials for wound healing have been summarized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 142 publications
0
5
0
Order By: Relevance
“…248 This includes the targeted delivery of oxygen and nutrients to the wound area and the generation of gradients of signalling molecules to direct cell migration and differentiation. [248][249][250][251] Huang et al developed a new method for creating fibres using microfluidic spinning technology that can carry two different types of cargo and release them when needed. 252 Fig.…”
Section: Wound Fluidmentioning
confidence: 99%
“…248 This includes the targeted delivery of oxygen and nutrients to the wound area and the generation of gradients of signalling molecules to direct cell migration and differentiation. [248][249][250][251] Huang et al developed a new method for creating fibres using microfluidic spinning technology that can carry two different types of cargo and release them when needed. 252 Fig.…”
Section: Wound Fluidmentioning
confidence: 99%
“…The process of wound healing can be divided into three stages, which include inflammatory, proliferative, and remodeling. In the early and entire phase of inflammation, the accelerated recruitment of cytokines and immune cells is very important. It has been shown that endogenous electric fields can promote the migration of macrophages, lymphocytes, and neutrophils to skin wound sites and ultimately promote wound healing .…”
Section: Applying Tengs-based Es For Promoting Wound Healingmentioning
confidence: 99%
“…Microfluidics, the science of manipulating multiphase fluids at the micro-nano scale, has been widely used in recent years to fabricate materials with specific fine structures and controlled compositions. 80 For example, due to its high reproducibility, flexibility, controllability, and low cost, microfluidics has been used to produce functional materials for wound healing 81 and achieve microcarrierization of oxygen-carrying materials such as hemoglobin 82 and perfluorocarbon. 83,84 In addition to conventional passive tissue-repairing materials like dressings, microfluidics can also produce micro-nano motors with active motility, 85,86 promising to break through the limitations of passive micronano materials for more flexible engineering regenerative applications.…”
Section: Microfluidic Techniquesmentioning
confidence: 99%